Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 29125 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Aves", { "or" : [ "Country is Suriname", "Country is French Guiana" ] }, "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 29125 records from 30 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0022360-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences